Diagnostic performance of CSF biomarkers in a well-characterized Australian cohort of sporadic Creutzfeldt-Jakob disease - Senesi, Matteo; Lewis, Victoria; Varghese, Shiji; Stehmann, Christiane; McGlade, Amelia; Doecke, James D.; Ellett, Laura; Sarros, Shannon; Fowler, Christopher J.; Masters, Colin L.; Li, Qiao-Xin; Collins, Steven J. (Frontiers in Neurology, 2023)
The most frequently utilized biomarkers to support a pre-mortem clinical diagnosis of sporadic Creutzfeldt–Jakob disease (sCJD) include concentrations of the 14-3-3 and total tau (T-tau) proteins, as well as the application of protein amplification techniques, such as the real time quaking-induced conversion (RT-QuIC) assay, in cerebrospinal fluid (CSF). Utilizing CSF from a cohort of neuropathologically confirmed (definite) sCJD (n = 50) and non-CJD controls (n = 48), we established the optimal cutpoints for the fully automated Roche Elecsys® immunoassay for T-tau and the CircuLexTM 14-3-3 Gamma ELISA and compared these to T-tau protein measured using a commercially available assay (INNOTEST hTAU Ag) and 14-3-3 protein detection by western immunoblot (WB). These CSF specimens were also assessed for presence of misfolded prion protein using the RT-QuIC assay. T-tau showed similar diagnostic performance irrespective of the assay utilized, with 90% sensitivity and specificity. The 14-3-3 protein detection by western blot (WB) has 87.5% sensitivity and 66.7% specificity. The 14-3-3 ELISA demonstrated 81.3% sensitivity and 84.4% specificity. RT-QuIC was the single best performing assay, with a sensitivity of 92.7% and 100% specificity. Our study indicates that a combination of all three CSF biomarkers increases sensitivity and offers the best chance of case detection pre-mortem. Only a single sCJD case in our cohort was negative across the three biomarkers, emphasizing the value of autopsy brain examination on all suspected CJD cases to ensure maximal case ascertainment.